ByzRev 05.2023.022: Daphne Penna – Roos Meijering (eds), A sourcebook on Byzantine law. Illustrating Byzantine law through the sources: (Medieval Law and Its Practice 34). Leiden – Boston: Brill 2022. 208 S. – ISBN 978-90-04-51470-6 - Chitwood, Zachary (The Byzantine Review, 2023)
Daphne Penna – Roos Meijering (eds), A sourcebook on Byzantine law. Illustrating Byzantine law through the sources (Medieval Law and Its Practice 34). Leiden – Boston: Brill 2022. 208 S. – ISBN 978-90-04-51470-6